PENGARUH NILAI TUKAR, UKURAN PERUSAHAAN DAN LEVERAGE KEUANGAN TERHADAP PROFITABILITAS (Studi Pada Bank BUMN Yang Terdaftar Di Bursa Efek Indonesia) - Risnaningsih Risnaningsih; Carmelinda Venansia Du Goma; Hendrik Suhendri (ITB AAS INDONESIA, 2022)
The purpose of this research is to directly determine the effect of the exchange rate, company size and financial leverage on profitability in state-owned banks as partially registered on the Stock Exchange. This research uses a quantitative descriptive method. In this research, the sample that will be used is a total sample of 4 State-Owned Enterprises banks that have been registered on the IDX. In this research, it is like using a financial report from 2014-2021. The data analysis technique that will be used is using multiple linear regression analysis. The results of this research prove that there is a significant influence on the profitability ratio in State-Owned Enterprise Banks as can be proven based on the Tcount = 3.128, company size can have a significant and significant effect on profitability in State-Owned Enterprise Banks with Tcount = 5,690 and financial leverage has a significant effect on profitability at state-owned banks with t count = 3.486. Banking companies in increasing profitability need to pay attention to financial leverage ratios and company size so that the company value is higher.